The Role of Education in Economic Growth: An Exploratory Literature Review - S. K. Kondybayeva; A. A. Sagynbayeva; G. M. Manarbek; K. Czerewacz-Filipowiczb (Экономика: стратегия и практика)
Human capital occupies a leading position in economic development and determines the importance of education as a system responsible for its production. Attention has increasingly been paid in recent years to the role of education in the economic growth of countries. Researchers began to study the impact of education on economic growth in the 19th century and continue to this day. Hence, the growth in the number of publications and scientific studies studying the importance of education in economic growth actualizes the need to use bibliometric analysis methods to identify patterns and trends studied by scientists from various countries around the world. The article examines the works of economists who formulated theories emphasizing the importance of education for economic development. This study reviews scientific works to determine the underlying concepts in the field of the role of education in economic growth. The purpose of this research is to analyze the structure and dynamics of academic research aimed at studying the role of education in economic growth. A bibliometric analysis of the literature was carried out using the VOSviewer software. The sample consists of 2,432 publications from the WoS database. A result of the analysis is a compiled bibliometric map of five clusters. The research outcomes apply to both local higher education establishments and governmental bodies responsible for state educational oversight.